Childhood depression: a bibliometric review - Graham Wetzell, Yin Victoria Zukha (2019)
This work presents a review of the literature about childhood depression (CD), during the period from 2010 to 2018. The used method has been the analysis of documents on this subject, which were identified in the ProQuest, EBSCO databases, articles of Google academic and digital books. A form and content analysis was conducted with the information obtained, also reviewing the following concepts: depression, childhood depression and factors that cause it. In this way, it has been found that the research about this subject, in the period indicated above, is still limited, especially at the national level, which is why it is necessary to promote the research of childhood depression in Peru from different fields of studies.